Instrument adaptation and validation for measuring satisfaction of information system users in Brazil (Gestão & Regionalidade, 2016)
This study aims to adapt the instrument created by Doll and Torkzadeh with empirical validation through the demonstrationof the satisfaction of end users of business management systems in Brazil. Results of exploratory factor analysis point tothe formation of six user satisfaction factors: accuracy, content, format, correctness, ease of use, and suitability. Factorsunderwent confirmatory factor analysis, which suggested exclusion of the suitability factor. The results were submitted tostructural equation modeling to shape the user satisfaction regarding the system, and the components "accuracy" and"ease of use" explain respectively 38.7% and 64.5% of the equation. Finally, an instrument composed by five factors and30 items was obtained. In general, the model, in its adaptation for Brazilian users, has proven effective for use as an informationsystems satisfaction diagnostic tool.